(untitled) (Journal of Partial Differential Equations, 1993)
In two-space-dimensional case we get the sharp lower bound of the life-span of classical solutions to the Cauchy problem with small initial data for fully nonlinear wave equations of the form &#x25fbu = F (u, Du, D_zDu) in which F(&#955) = O(|&#955|^1+&#945) with &#945 = 2 in a neighbourhood of &#955 = 0. The cases &#945 = 1 and &#945 &#8805 3 have been considered respectively in [1] and [2].